-6q=-5q+7

Simple and best practice solution for -6q=-5q+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6q=-5q+7 equation:


Simplifying
-6q = -5q + 7

Reorder the terms:
-6q = 7 + -5q

Solving
-6q = 7 + -5q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '5q' to each side of the equation.
-6q + 5q = 7 + -5q + 5q

Combine like terms: -6q + 5q = -1q
-1q = 7 + -5q + 5q

Combine like terms: -5q + 5q = 0
-1q = 7 + 0
-1q = 7

Divide each side by '-1'.
q = -7

Simplifying
q = -7

See similar equations:

| 2ab(5a-7b)= | | x/2-x/3=5/6 | | 7(x^2-4)+2x=2(x-4) | | 8x^3+20x^3+12x=0 | | u^2-10u+25= | | 2-3h=10-5h | | 10-6t=-8-9t | | 8-8x=1-3x | | 4=-v+v/-8 | | -7-5u=-7u+9 | | 4a^2-9a+2=0 | | 9+3g=4g | | 6y+5=4y-9 | | -4-9=-2 | | 5(6x-5)=1-1x | | -5n=5-10n | | 4b+10=-10+2b | | -5w-10=3w+6 | | 8x=100+3x | | 5x+35=2(x+8) | | 2r-6=3r | | S=187+0.225S | | 10-2z=-7z | | -f+3=-4f | | 7*3x=6x+9 | | x+1/3+x-2/6=x+6/12 | | -6j-8=-8j | | 1/4d+3/4=6 | | x+6/3+x-2/6=2x-3/12 | | 27=2-5(9-x) | | 3(t+1)=9 | | 1/2h-16=5/8h |

Equations solver categories